Membangun Keluarga Harmonis Berlandaskan Nilai-Nilai Kepesantrenan: Studi Naskah Manuskrip Risalatun Muhimmah Peninggalan KH. Abd. Rahman Gapura - Fathor Rahman; Abd. Warits; Moh. Syahirul Alim (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2026)
The high divorce rate in Indonesia, including in Sumenep Regency, indicates the need to strengthen the foundations of a harmonious family. This study aims to examine the concept of a harmonious family and pesantren values in the manuscript Ris?latun Muhimmah by KH. Abdurrahman Gapura, as well as to analyse its relevance in the contemporary era. The method used is qualitative with a philological approach to critique the manuscript and a thematic-contextual approach to analyse its content. The results of the study reveal that the concept of a harmonious family in this manuscript is built on a balance of husband and wife's rights and obligations, which are based on obedience to Allah, love and noble character. This manuscript also represents core pesantren values such as sincerity, humility, simplicity, togetherness, and independence. The integration of these values into modern family life is considered highly relevant for building household resilience and responding to social challenges based on local pesantren wisdom. This research concludes that Ris?latun Muhimmah offers a solution-oriented model rooted in the intellectual heritage of pesantren to strengthen the foundation of the family. Keywords: Harmonious Family, Pesantren Values, Ris?latun Muhimmah, Manuscript Study.